Peran Statistik dalam Meningkatkan Kualitas Penelitian Pendidikan - Innaya Meidini Sastri; Nadia Koesvahana; Jesi Alexander Alim; Mitha Dwi Anggriani (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the role of statistics in enhancing the quality of educational research. Statistics serve as a scientific foundation that not only provide analytical tools but also reinforce the validity, reliability, and objectivity of research outcomes. Using a descriptive qualitative approach through a literature review, the study reviews scholarly works highlighting how statistics support various research stages, including sampling, instrument development, data processing, and analysis. Findings show that applying statistics allows educational research to be more evidence-based, measurable, and accountable. However, challenges remain, both in Indonesia and globally, such as limited data quality, institutional coordination, human resource capacity, and adaptation to digital technologies. To address these issues, strengthening statistical literacy and regulations is essential so that statistical data remain relevant and support evidence-based education policies.